Leukocytosis after routine cranial surgery: A potential marker for brain damage in intracranial surgery - Agrawal, Deepak; Kurwale, Nilesh; Sharma, Bhawani (Asian Journal of Neurosurgery, 2016)
Aims and Objectives: Leukocytosis after intracranial surgery may create concern about possible infection, especially when associated with fever. Knowledge of the expected degree of leukocytosis after surgery would assist in the interpretation of leukocytosis. It was hypothesized that the degree of leukocytosis after intracranial surgery correlated with the extent of brain damage inflicted during the surgery. Materials and Methods: In this prospective study conducted over 6 months, consecutive patients undergoing either elective resections of brain tumors (having significant collateral brain damage) or aneurysm clipping (with minimal collateral brain damage) were studied. Total blood leukocyte count was checked daily in the morning for the first five postoperative days in both the groups. The mean of the leukocyte count ratio (postoperative leukocyte count/preoperative leukocyte count) on each day was calculated for each group. Results: There were 76 patients, 46 in the test group and 30 controls. Both groups were well matched in age, sex, duration of surgery, and intraoperative fluid balance. The mean leukocyte count ratio on POD1 in the tumor group was significantly higher (1.87) as compared to 1.1 in the aneurysm group (P = 0.001). This difference in the leukocyte count ratio between the groups was maintained on the second and third postoperative days, with decreasing level of significance after the third day. Conclusions: This study shows that intraoperative brain injury is associated with leukocytosis in the immediate postoperative period. This can assist in the interpretation of leukocytosis after intracranial surgeries and could be a quantitative marker for brain injury in patients undergoing intracranial surgery.
Keywords: Brain damage; brain injury; brain tumor; intracranial surgery; leukemoid reaction; leukocytosis; marker; total leukocyte count